Ganymede's Ionosphere Observed by a Dual‐Frequency Radio Occultation With Juno. Issue 23 (12th December 2022) - Buccino, D. R.; Parisi, M.; Gramigna, E.; Gomez‐Casajus, L.; Tortora, P.; Zannoni, M.; Caruso, A.; Park, R. S.; Withers, P.; Steffes, P.; Hodges, A.; Levin, S.; et al.
Abstract: In June 2021, the Juno spacecraft executed a close flyby of Ganymede. During the encounter, Juno passed behind Ganymede for 15 min as observed from Earth, providing the geometry to conduct a radio occultation experiment to probe Ganymede's tenuous ionosphere. X‐band and Ka‐band radio links were transmitted from Juno to antennas at the Deep Space Network. Electrons encountered along the radio propagation path advance the signal's phase and a linear combination the two frequencies allows for a direct measurement of the electron content along the propagation path. On occultation ingress, an ionosphere peak of 2, 000 ± 500 (1‐σ) cm −3 near the surface was observed. On occultation egress, no statistically significant ionosphere was detected. Ingress observation viewed where Ganymede's intrinsic magnetic field lines are open whereas egress observation viewed where the field lines are closed, implying electron impact ionization plays a key role in the generation of the ionosphere. Plain Language Summary: Juno conducted a flyby of Ganymede, the largest Galilean moon of Jupiter, on 7 June 2021. During the flyby, the Juno spacecraft set behind Ganymede as observed by the Earth. Juno's radio signals were captured by the Deep Space Network during this time to make radio occultation measurements of Ganymede's ionosphere. Elevated electron density was measured on occultation ingress but no statistically significant ionosphere was detected on egress. These results are consistent with Galileo's radio occultation observations and provide insight into the generation mechanisms of Ganymede's ionosphere. Key Points: A dual‐frequency radio occultation experiment of Ganymede's ionosphere was conducted with the Juno spacecraft on 7 June 2021 Ingress observed an ionosphere with peak density 2, 000 ± 500 (1‐σ) cm −3 but no statistically significant signature was detected on egress Ingress detection occurred in the open field line region, where higher electron impact ionization rates may increase the electron density